Wheat : The crop of past, present and future generations in India - Singh, S S; Yadav, Rajbir; Singh, G P; Jain, Neelu (Indian Farming, 2015)
Wheat is widely distributed and largely traded because of special properties of its protein. The viscoelastic nature of its protein provides its dough strength to be amended in the various products. Its wide distribution and adaptability along with ease in storage and properties of its dough make it as major diet component for human being throughout the world. Besides food, low grade wheat unsuitable for human consumptions used for animal feed, making adhesives, paper additives and alcoholic beverages.